sTREM2 mediates the associations of minimal depressive symptoms with amyloid pathology in prodromal Alzheimer’s disease: The CABLE study - Zhi-Bo Wang; Yan Sun; Ya-Hui Ma; Yan Fu; Hao Hu; Wei Xu; Zuo-Teng Wang; Ling-Zhi Ma; Lan Tan; Jin-Tai Yu (Translational Psychiatry, 2022)
Abstract The effects of microglial activation on the associations between depression and Alzheimer’s disease (AD) are still unclear. TREM2 gene plays a pivotal role in microglial activation, has been identified as a risk factor for AD. In this work, we aimed to assess the interrelationships of soluble TREM2 (sTREM2) level in cerebrospinal fluid (CSF), minimal depressive symptoms (MDSs), and CSF amyloid markers. The linear regression analyses were conducted on 796 cognitively unimpaired participants from the CABLE (Chinese Alzheimer’s Biomarker and LifestylE) study. Causal mediation analyses with 10,000 bootstrapped iterations were used to test the mediation effects. In addition, similar statistical analyses were performed in subgroups stratified by sex, age, and APOE ε4 carrier status. In total subjects, MDSs were associated with lower CSF sTREM2 levels (p < 0.0001), lower CSF amyloid markers (p < 0.0001), and poorer cognitive performance (MMSE, p = 0.0014). The influence of MDSs on CSF amyloid markers was partially mediated by CSF sTREM2 (proportion from 2.91 to 32.58%, p < 0.0001). And we found that the sTREM2-amyloid pathway partially mediated the effects of MDSs on cognition. Of note, exploratory subgroup analyses showed that the above influences of CSF sTREM2 were pronounced in the APOE ε4 (−) group. These results suggest that early depression is associated with amyloid pathology, which might be partly mediated by microglial activation, especially in the absence of APOE ε4.